2014
DOI: 10.1039/c4cp00678j
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrochemical properties of ethynylaniline derivatives of phenothiazine, phenothiazine-5-oxide and phenothiazine-5,5-dioxide

Abstract: Modifications in the sulfur oxidation state of phenothiazine results in dramatic changes to the excited-state geometry with little effect on the HOMO energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Owing to their ubiquitous nature, it is unsurprising that organic compounds constitute as ignificant group within the EC materials currently available. This includes the popularc lass of molecules known as the viologens, [2,12,13] as well as many other types of organic systems such as conducting polymers (e.g., PEDOT,p olyaniline, polythiophene), [6,[14][15][16] phenothiazine derivatives, [17,18] perylene and relatedd iimides, [19][20][21] and others. [22,23] We have recently reported that the one-electrone lectrochemicalr eduction of aromatic oxygen and sulfur para-substituted diesters induces intense colorc hanges, and have estimated their contrastr atios and chromatic efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their ubiquitous nature, it is unsurprising that organic compounds constitute as ignificant group within the EC materials currently available. This includes the popularc lass of molecules known as the viologens, [2,12,13] as well as many other types of organic systems such as conducting polymers (e.g., PEDOT,p olyaniline, polythiophene), [6,[14][15][16] phenothiazine derivatives, [17,18] perylene and relatedd iimides, [19][20][21] and others. [22,23] We have recently reported that the one-electrone lectrochemicalr eduction of aromatic oxygen and sulfur para-substituted diesters induces intense colorc hanges, and have estimated their contrastr atios and chromatic efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…It was found computationally that analogous to 2a, the core of p-extended compound 4a maintains its planarity, while the core of 4b is bent in a similar fashion to parent compound 2b. In a previous report 19 of a related compound whereby the carbonyl of 4a was replaced with a sulfoxide, the ground state and excited state structures showed large changes. The same computational study of ground state and excited state optimized geometries were carried out here with 4a and 4b and showed minimal structural change in the ground versus excited states.…”
Section: Synthesis and Structurementioning
confidence: 94%
“…Knoevenagel condensations of 2a and 3a with malononitrile 13 resulted in the analogous dicyanomethylene precursors 2b and 3b, respectively, in approximately 70% yield. Both dibromo-precursors, 3a and 3b, were subjected to Sonogashira cross coupling conditions with N-dialkylated-ethynylaniline 19,27 to produce the two D-A-D chromophores 4a and 4b, in 58% and 73% yield, respectively. Single crystals of the final compounds were elusive.…”
Section: Synthesis and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, they have a planar structure when they have positive charges. A recent report also indicated planarity of phenothiazine rings increases in their excited state [16]. According to Cambridge Structural Database (CSD) [17], 26 structures of planar phenothiazines have been reported, including those of 22 charged phenothiazines.…”
Section: Introductionmentioning
confidence: 99%